2017
DOI: 10.1111/cei.13016
|View full text |Cite
|
Sign up to set email alerts
|

Altered levels of soluble CD18 may associate immune mechanisms with outcome in sepsis

Abstract: The pathogenesis of sepsis involves a dual inflammatory response, with a hyperinflammatory phase followed by, or in combination with, a hypoinflammatory phase. The adhesion molecules lymphocyte function-associated antigen (LFA-1) (CD11a/CD18) and macrophage-1 (Mac-1) (CD11b/CD18) support leucocyte adhesion to intercellular adhesion molecules and phagocytosis through complement opsonization, both processes relevant to the immune response during sepsis. Here, we investigate the role of soluble (s)CD18 in sepsis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 45 publications
0
11
0
Order By: Relevance
“…On the other hand, integrins are required for host defense, demonstrated by the requirement for Mac-1 to clear bacteria 22 – 24 , 51 . Clinically, blood concentrations of soluble CD40L 52 and sCD18 53 are associated with sepsis, suggesting that both, Mac-1 and CD40L, participate in the acute inflammatory response in sepsis. To outweigh its conflicting effects on host defense and pathologic inflammation, we hypothesized that a ligand-specific blockade would be superior to an unspecific inhibition of Mac-1 in polymicrobial sepsis.…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, integrins are required for host defense, demonstrated by the requirement for Mac-1 to clear bacteria 22 – 24 , 51 . Clinically, blood concentrations of soluble CD40L 52 and sCD18 53 are associated with sepsis, suggesting that both, Mac-1 and CD40L, participate in the acute inflammatory response in sepsis. To outweigh its conflicting effects on host defense and pathologic inflammation, we hypothesized that a ligand-specific blockade would be superior to an unspecific inhibition of Mac-1 in polymicrobial sepsis.…”
Section: Resultsmentioning
confidence: 99%
“…One important observation made, so far only by Gjelstrup et al is the oligomeric state of the sCD18 species ( 45 ). It is likely that the oligomerization enables a strong, polyvalent interaction with ligand-coated surfaces such as the tested surfaces with ICAM-1 ( 44 46 ) and iC3b ( 48 ). It was observed that recombinant sCR3 fragments oligomerize ( 49 ), but the relationship between these oligomers ( 45 ) with the oligomer forms found in plasma remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Further, disease remission in early rheumatoid arthritis is associated with increased sCD18 levels 26 . Finally, very high and very low levels of sCD18 levels were recently associated with fatal outcomes in critically ill sepsis patients 27 . Therefore, changes in sCD18 levels seems to be part of the inflammatory response in general.…”
Section: Discussionmentioning
confidence: 99%